Extending Voice and Autonomy through Participatory Action Research: Ethical and Practical Issues: Reflections on a Workshop held at Durham University, November 2018. Issue 2 (2nd April 2020) - Kong, Sui Ting; Banks, Sarah; Brandon, Toby; Chappell, Stewart; Charnley, Helen; Hwang, Se Kwang; Rudd, Danielle; Shaw, Sue; Slatcher, Sam; Ward, Nicki
ABSTRACT: Participatory action research always operates in the tension of extending the voice of people who are marginalised and unheard in the society. A workshop, 'Extending Voice and Autonomy through Participatory Action Research: Ethical and Practical Issues', was therefore organised to look at the issues arising from this tension. The workshop aimed to examine critically the potential of participatory action research to enable people whose voices are seldom heard and choices are often restricted to be seen, heard and to influence practice and policy relevant to their lives. The paper first outlines the rationale for the workshop and then demonstrates how 'co-impact' of participatory action research projects can be achieved through having conversations and reflecting on the ideas of 'voice and autonomy', 'knowledge', 'vulnerability', 'user involvement and participation'. Through reflecting on the experience of preparing for and delivering the workshop, we seek ways to transform the relationship(s) between service users/community partners and academic and service professionals in the hope of generating practical knowledge ethically.